Access to justice, culture and online dispute resolution - Osna, Gustavo (2019)
It is undeniable that over the last decades the idea of alternative dispute resolution (ADR) started to receive more attention. In this sense, such aspect has been recurrently confronted with the guarantee of access to justice, verifying their compatibility. The present study observes this element, investigating, specifically, the inevitable role that the techniques of online dispute resolution (ODR) might play in our reality. This, particularly, due to the cultural nature of civil procedure.